Malaysian Journal of Library and Information Science 1996-2000: a bibliometric study - Tiew, W.S.; Abrizah, Abdullah; Kaur, Kiran (Department of Library & Information Science, Faculty of Arts and Social Sciences, Universiti Malaya, 2002)
A bibliometric examination of all the journal articles published in the Malaysian Journal of Library & Information Science from 1996-2000 was carried out. The range of articles published per volume is between 14 and 17; average number of references per article is 22.5; the average length per article is 41.2 pages; 53(69.74%) of the articles are research oriented; the percentage of multi-authored papers is slightly higher at 52.6% or 40 papers out of a total of 76; the most prolific author contributed 12 articles; 36 (45%) of the authors are geographically affiliated to Malaysia; authors affiliated to library schools were well represented (55.2%); the most productive institution is Faculty of Computer Science and Information Technology, University of Malaya with 26 out of 80 author’s affiliation; the most popular subject is Scientific and Professional Publishing; 30 (39.5%) articles contained author’s self-citation, while the rate of journal self-citation is found to be 27.6% and most of the articles (67.1%) contained no formal acknowledgement.